The Implementation Contextual Teaching Learning to Improve Students' Speaking Skill: Penerapan CTL untuk meningkatkan kemampuan berbicara siswa - Fauziyah, Fina; Ida Royani; Adis Triawan; M. Ibnu Nabil; Niken Kencono Ungu (Journal of Language Education (JoLE), 2024)
Speaking is an important skill in language learning, while Contextual Teaching and Learning (CTL) is an approach that places emphasis on the relevance of learning in the context of students' real-life experiences. This study examines the impact of implementing CTL on students' speaking abilities. By integrating social context, culture, and daily experiences, students are more motivated to engage in speaking activities. The methodology employed encompasses observations, interviews, and an analysis of learning outcomes. The results demonstrated that the implementation of CTL significantly enhanced students' confidence in speaking and their communication skills. The findings suggest that a contextual approach can be an effective strategy for learning speaking, thereby encouraging students to be more active and relevant in communicating.